Crenças atribuídas à opção de não usar MDMA (ecstasy): estudo qualitativo entre não usuários, usuários experimentais e ex-usuários - Comis, Maria Angélica de Castro [UNIFESP] (2011)
Introduction: Although ecstasy (MDMA) is a drug mostly consumed in the eletronic scene context, not all individuals who faces an opportunity to use ecstasy do it. This study aimed at understanding the reasons ascribed to not using or stop using ecstasy in order to contribute to preventive actions or damage reduction activities. Methods: Snowball sampling was applied. By means of individual semi-structured interview, 53 participants were allocated in three groups: non-users (NU, n = 23), experimental users (EXP, n = 12) and ex-users (EX-US, n = 18). Literal transcriptions were submitted to content analyses using NVivo8. Results: Non-users (NU) and experimental users (EXP) attributed reasons mostly related to fear of effects and moral, family or religious principles. Ex-users (EX-U) claimed reasons related to health complications and being apart from the context of use, but they did not discard the possibility of future use. Aspects related to health, values and context were present at all groups. Final considerations: Negative effects and/or adverse consequences seem to lead the decisions among the different groups, and such information should be used by universal preventive actions. For those who have already used ecstasy, both social and environmental context seem to be the most important factors for decision making, evidencing the importance of context for selective prevention and damage reduction actions.